2014
DOI: 10.3109/00016357.2014.926023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic evaluation of the efficacy of platelet-rich plasma combined with hydroxyapatite bone graft substitutes in the treatment of intra-bony defects in maxillofacial region

Abstract: Combined use of PRP and bovine-derived HA graft materials for the treatment of intra-bony defects might be an appropriate approach when the main goal is providing earlier bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Since PRP is an easy obtaining cost-effective source of growth factors, it has been used in combination with grafts and other natural and synthetic scaffolds such as hydroxyapatite, coral skeleton, chitosan, polymers and hydrogels (Roffi et al 2013;Oryan et al 2014;Salamanna et al 2015). Durmuslar et al (2014) assessed bovine hydroxyapatite, PRP and resorbable collagen membranes for the treatment of intra-bony defects and reported healing acceleration. In another study, Schneppendahl et al (2015) evaluated an autograft and PRP in a diaphyseal bone defect and obtained desired histomorphometric and radiographic results.…”
Section: Discussionmentioning
confidence: 99%
“…Since PRP is an easy obtaining cost-effective source of growth factors, it has been used in combination with grafts and other natural and synthetic scaffolds such as hydroxyapatite, coral skeleton, chitosan, polymers and hydrogels (Roffi et al 2013;Oryan et al 2014;Salamanna et al 2015). Durmuslar et al (2014) assessed bovine hydroxyapatite, PRP and resorbable collagen membranes for the treatment of intra-bony defects and reported healing acceleration. In another study, Schneppendahl et al (2015) evaluated an autograft and PRP in a diaphyseal bone defect and obtained desired histomorphometric and radiographic results.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of platelets-rich plasma combined with bovine hydroxyapatite bone graft and resorbable membrane was investigated both clinically and radiographically for the treatment of intrabony pockets on the distal aspect of L2M following the surgical extraction of fully impacted L3M. The study concluded that the combined use of platelet-rich plasma with bovine hydroxyapatite bone graft materials for the treatment of intrabony defects might be an appropriate approach when the main goal is providing earlier bone regeneration [ 15 ]. Another combination that included platelet-rich plasma and a resorbable membrane of procaine origin (Bio-Gide; Geistlich Biomaterials, Wolhusen, Switzerland) was investigated in a randomized controlled trial in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent periodontal pocket formation and promote uneventful bony healing, grafting with biomaterials can be considered [16,17]. Autogenous bone is generally considered the gold standard for bone graft, and synthetic materials such as hydroxyapatite are considered an alternative for the reconstruction of the extraction socket [18]. Ridge preservation materials have been used as filling materials for the extraction socket.…”
Section: Introductionmentioning
confidence: 99%